The Role of Advertising and Sales Promotion in Shaping Community Interest in Islamic Bank Transactions - Amir Yahya; Anisya Citra Amelia; Saprudin Saprudin; Ita Sitasari; Emmy Hamidiyah (International Journal of Informatics, Economics, Management and Science, 2026)
This study investigates the influence of advertising and sales promotion on community interest in conducting transactions at Islamic banks, with a focus on residents of Tegalsari Village. In the context of increasing competition within the banking sector, effective marketing strategies are essential, particularly for Islamic banks that operate based on distinct principles and values. This research adopts a quantitative approach using a survey method, involving 100 respondents selected from the local community. Data were collected through structured questionnaires and analyzed using multiple linear regression to test the proposed hypotheses. The results indicate that advertising has a positive and significant effect on public interest in transacting with Islamic banks. In addition, sales promotion is also found to significantly enhance community interest. These findings suggest that attractive advertising and well-targeted promotional activities play an important role in increasing public engagement with Islamic banking services. This study provides practical insights for Islamic bank management in developing effective marketing strategies and contributes to the literature on Islamic banking marketing